Assessing hydrochar wash-water toxicity: screening strategies for reducing toxicity from food waste-derived hydrochars - Andres Sarrion; Jasmine R. Flora; Joseph R.V. Flora; Ramesh Goel; Lubo Liu; Perry J. Pellechia; Elena Diaz; Angel F. Mohedano; Nicole D. Berge (Waste Management, 2026)

Cloudburst or hybrid phenomenon? Dissecting the Dharali flood disaster of 2025 - Gopika Vijayalekshmi; N. K. Goel; Manohar Arora; M. L. Sharma; R. Unni Narayanan; R. K. Vishnoi (Hydrological Sciences Journal, 2026)

The global proliferation of aquatic, benthic Microcoleus: Taxonomy, distribution, toxin production, ecology, and future directions - Laura T. Kelly; Daniel G. Beach; Joanna R. Blaszczak; Keith Bouma-Gregson; Sydney M. Brown; Haowu Cheng; Janette L. Davidson; Jutta Fastner; Marcus Francis; Andrea Garcia Jimenez; Laurel Genzoli; Ramesh Goel; et al. (Water Research, 2026)

Ameliorative effect of glycyrrhizin in mitochondrial drug-resistant epilepsy: role of HMGB1 inhibition - Arvinder Kaur; Tushar Anshu; R. K. Goel (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

The natural products magnetic resonance database (NP-MRD): comprehensive resource for natural products NMR data enabling discovery and understanding - John R. Cort; Jessica L. Bade; Roger G. Linington; Matthew Pin; Ella F. Poynton; Lloyd W. Sumner; James T. Koller; Zachary M. Tretter; Bharat Goel; David S. Wishart; Vasuk Gautam; Scott McKay; et al. (Phytochemistry Letters, 2025)

Room for education: Undergraduate students associate plastic surgery primarily with aesthetic procedures - Charlotte R. Reed; Bradley A. Melnick; Gretchen A. O’Connor; Rena A. Li; Tokoya Williams; Chirag Goel; Robert D. Galiano (Next Research, 2025)

Convolutional Neural Networks for Mineral Prospecting Through Alteration Mapping with Remote Sensing Data - Ehsan Farahbakhsh; Dakshi Goel; Dhiraj Pimparkar; R. Dietmar Müller; Rohitash Chandra (PFG – Journal of Photogrammetry, Remote Sensing and Geoinformation Science, 2025)
Traditional geological mapping methods, which rely on field observations and rock sample analysis, are inefficient for continuous spatial mapping of geological features such as alteration zones. Deep learning models such as convolutional neural networks (CNNs) have ushered in a transformative era in remote sensing data analysis. CNNs excel in automatically extracting features from image data for classification and regression problems. CNNs have the ability to pinpoint specific mineralogical changes attributed to mineralisation processes by discerning subtle features within remote sensing data. In this study, we deploy CNNs with three sets of remote sensing data, namely Landsat 8, Landsat 9, and ASTER, to delineate diverse alteration zones within a mineral-rich region north of Broken Hill in western New South Wales, Australia. Our methodology involves model training using two distinct sets of training samples generated through ground truth data and a fully automated approach through selective principal component analysis (PCA). We also compare CNNs with conventional machine learning models, including k‑nearest neighbours, support vector machines, and multilayer perceptron. Our findings indicate that training with a ground truth-based dataset produces more reliable alteration maps. Additionally, we find that CNNs perform slightly better when compared to conventional machine learning models, which further demonstrates the ability of CNNs to capture spatial patterns in remote sensing data effectively. We find that Landsat 9 surpasses Landsat 8 in mapping iron oxide areas when employing the CNNs model trained with ground truth data obtained by field surveys. We also observe that using ASTER data with the CNNs model trained on the ground truth-based dataset produces the most accurate maps for two other important types of alteration zones, argillic and propylitic. This underscores the utility of CNNs in enhancing the efficiency and precision of geological mapping, particularly in discerning subtle alterations indicative of mineralisation processes, especially those associated with critical metal resources.

Growth and anatoxin-a production of Microcoleus (Cyanobacteria) strains from streams in California, USA - Sydney M. Brown; Joanna R. Blaszczak; Robert K. Shriver; R.Christian Jones; Abeer Sohrab; Ramesh Goel; Gregory L. Boyer; Bofan Wei; Kalina M. Manoylov; T.Reid Nelson; Jordan M. Zabrecky; Rosalina Stancheva (Harmful Algae, 2025)

Site-specific characterisation of hydrogeological parameters for low-level solid radioactive waste disposal facility at Tarapur, India - Shelly Goel; Manish Chopra; Aditi C Patra; Faby Sunny; G Ganesh; R B Oza; M S Kulkarni (Journal of Earth System Science, 2023)

Ada-GridRF: A Fast and Automated Adaptive Boost Based Grid Search Optimized Random Forest Ensemble model for Lung Cancer Detection - Ananya Bhattacharjee; R. Murugan; Badal Soni; Tripti Goel (Physical and Engineering Sciences in Medicine, 2022)

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

The Built Environment and Health in Low- and Middle-Income Countries: a Review on Quantitative Health Impact Assessments - M. Thondoo; R. Goel; L. Tatah; N. Naraynen; J. Woodcock; Mark Nieuwenhuijsen (Current Environmental Health Reports, 2022)

Spelling Out CICs: A Multi-Organ Examination of the Contributions of Cancer Initiating Cells’ Role in Tumor Progression - Shivani Baisiwala; Shreya Budhiraja; Chirag Goel; Khizar R. Nandoliya; Miranda R. Saathoff; Atique U. Ahmed (Stem Cell Reviews and Reports, 2022)

A novel four-step feature selection technique for diabetic retinopathy grading - N. Jagan Mohan; R. Murugan; Tripti Goel; Seyedali Mirjalili; Parthapratim Roy (Physical and Engineering Sciences in Medicine, 2021)

Comprehensive Airborne Laser Scanning (ALS) Simulation - Shikhar Dayal; Salil Goel; Bharat Lohani; Namit Mittal; R. K. Mishra (Journal of the Indian Society of Remote Sensing, 2021)

Development of mixed anaerobic culture for degrading high concentrations of chlorophenols - M. Goel; M. Ramesh; J. S. Sudarsan; R. Kanawade; S. Nithiyanantham (International Journal of Environmental Science and Technology, 2020)

Prediction of Ground Behaviour for Rock Tunnelling - R. D. Dwivedi; R. K. Goel; M. Singh; M. N. Viladkar; P. K. Singh (Rock Mechanics and Rock Engineering, 2019)

Insights into direct interspecies electron transfer mechanisms for acceleration of anaerobic digestion of wastes - D. Sharma; R. Mahajan; G. Goel (International Journal of Environmental Science and Technology, 2019)

Evaluating anaerobic and aerobic digestion strategies for degradation of pretreated pine needle litter - R. Mahajan; A. Nikitina; Y. Litti; A. Kallistova; A. Nozhevnikova; G. Goel (International Journal of Environmental Science and Technology, 2019)

Genome-Wide Analysis in Wild and Cultivated Oryza Species Reveals Abundance of NBS Genes in Progenitors of Cultivated Rice - Hukam C. Rawal; S. V. Amitha Mithra; Kirti Arora; Vishesh Kumar; Neha Goel; Dwijesh Chandra Mishra; K. K. Chaturvedi; Anil Rai; S. Vimala Devi; T. R. Sharma; Amolkumar U. Solanke (Plant Molecular Biology Reporter, 2018)

Matrix-assisted laser desorption ionization time of flight mass spectrometry (MALDI-TOF MS) for rapid identification of micro-organisms in the routine clinical microbiology laboratory - C. Wattal; J. K. Oberoi; N. Goel; R. Raveendran; S. Khanna (European Journal of Clinical Microbiology & Infectious Diseases, 2017)

Development of an efficient, genotype independent plant regeneration and transformation protocol using cotyledonary nodes in safflower (Carthamus tinctorius L.) - V. Patial; R. Krishna; G. Arya; V. K. Singh; M. Agarwal; S. Goel; A. Jagannath; A. Kumar (Journal of Plant Biochemistry and Biotechnology, 2016)

Scale dependency of dynamic relative permeability–satuartion curves in relation with fluid viscosity and dynamic capillary pressure effect - Gaurav Goel; Luqman K. Abidoye; Bhagu R. Chahar; Diganta B. Das (Environmental Fluid Mechanics, 2016)

Numerical study of a buoyant plume from a multi-flue stack into a variable temperature gradient atmosphere - Ratna Kishore Velamati; M. Vivek; K. Goutham; G. R. Sreekanth; Santosh Dharmarajan; Mukesh Goel (Environmental Science and Pollution Research, 2015)

Assessment of genetic diversity in indigenous turmeric (Curcuma longa) germplasm from India using molecular markers - Sushma Verma; Shweta Singh; Suresh Sharma; S. K. Tewari; R. K. Roy; A. K. Goel; T. S. Rana (Physiology and Molecular Biology of Plants, 2015)

Allocation in life cycle inventory: partial set of solutions to an ill-posed problem - Nathan B. Cruze; Prem K. Goel; Bhavik R. Bakshi (The International Journal of Life Cycle Assessment, 2014)

Revisiting least squares techniques for the purposes of allocation in life cycle inventory - Nathan B. Cruze; Prem K. Goel; Bhavik R. Bakshi (The International Journal of Life Cycle Assessment, 2014)

Design, synthesis, and PASS-assisted evaluation of novel 2-substituted benzimidazole derivatives as potent anthelmintics - Kamalpriya Garg; Yogita Bansal; Gulshan Bansal; R. K. Goel (Medicinal Chemistry Research, 2014)

Water pollution of Sabarmati River—a Harbinger to potential disaster - Soumya Haldar; Subir Kumar Mandal; R. B. Thorat; Sangita Goel; Krushnakant D. Baxi; Navalsang P. Parmer; Vipul Patel; S. Basha; K. H. Mody (Environmental Monitoring and Assessment, 2014)

Occurrence and distribution of selected heavy metals and boron in groundwater of the Gulf of Khambhat region, Gujarat, India - Devang Upadhyaya; Mayur D. Survaiya; Shaik Basha; Subir K. Mandal; R. B. Thorat; Soumya Haldar; Sangita Goel; Himal Dave; Krushnakant Baxi; Rohit H. Trivedi; Kalpana H. Mody (Environmental Science and Pollution Research, 2014)

Assessment of genetic diversity in Indian rice germplasm (Oryza sativa L.): use of random versus trait-linked microsatellite markers - SHEEL YADAV; ASHUTOSH SINGH; M. R. SINGH; NITIKA GOEL; K. K. VINOD; T. MOHAPATRA; A. K. SINGH (Journal of Genetics, 2013)

Curative effect of Terminalia chebula extract on acetic acid-induced experimental colitis: role of antioxidants, free radicals and acute inflammatory marker - M. K. Gautam; Shalini Goel; R. R. Ghatule; A. Singh; G. Nath; R. K. Goel (Inflammopharmacology, 2013)

On the “rigorous proof of fuzzy error propagation with matrix-based LCI” - Nathan Cruze; Prem K. Goel; Bhavik R. Bakshi (The International Journal of Life Cycle Assessment, 2013)

Genetic structure and diversity of India hybrid tea - S. N. Raina; P. S. Ahuja; R. K. Sharma; S. C. Das; P. Bhardwaj; R. Negi; V. Sharma; S. S. Singh; R. K. Sud; R. K. Kalia; V. Pandey; J. Banik; et al. (Genetic Resources and Crop Evolution, 2012)

Growth and metabolic responses of maize (C 4 species) and rice (C 3 species) genotypes to cadmium toxicity - S. Goel; J. Malik; R. Awasthi; R. Sandhir; H. Nayyar (Cereal Research Communications, 2012)

Unravelling the antimetastatic potential of pentoxifylline, a methylxanthine derivative in human MDA-MB-231 breast cancer cells - Peeyush N. Goel; R. P. Gude (Molecular and Cellular Biochemistry, 2011)

Role of Vitamin D Supplementation in Hypertension - R. K. Goel; Harbans Lal (Indian Journal of Clinical Biochemistry, 2011)

Molecular characterization of a new isolate of phytoplasma associated with malformation and twisting of floral spikes of Gladiolus in India - S. K. Raj; S. K. Snehi; M. S. Khan; M. H. Asif; S. K. Bag; R. K. Roy; A. K. Goel (Journal of General Plant Pathology, 2010)

Anti-inflammatory, analgesic and antipyretic activity of aqueous extract of fresh leaves of Coccinia indica - Junaid Niazi; Parabhdeep Singh; Yogita Bansal; R. K. Goel (Inflammopharmacology, 2009)

Climate Variability Influences on Hydrological Responses of a Large Himalayan Basin - Manohar Arora; Pratap Singh; N. K. Goel; R. D. Singh (Water Resources Management, 2008)

Transfer of leaf rust and stripe rust resistance from Aegilops umbellulata Zhuk. to bread wheat (Triticum aestivum L.) - Parveen Chhuneja; Satinder Kaur; R. K. Goel; M. Aghaee-Sarbarzeh; M. Prashar; H. S. Dhaliwal (Genetic Resources and Crop Evolution, 2008)

Mapping of adult plant stripe rust resistance genes in diploid A genome wheat species and their transfer to bread wheat - Parveen Chhuneja; Satinder Kaur; Tosh Garg; Meenu Ghai; Simarjit Kaur; M. Prashar; N. S. Bains; R. K. Goel; Beat Keller; H. S. Dhaliwal; Kuldeep Singh (Theoretical and Applied Genetics, 2008)

Poster abstracts - J. Ferrie; M. Shipley; F. Cappuccio; E. Brunner; M. Miller; M. Kumari; M. Marmot; A. Coenen; J. L. Castillo; F. Araya; G. Bustamante; L. Montecino; et al. (Sleep and Biological Rhythms, 2007)

Bacterial laccases - P. Sharma; R. Goel; N. Capalash (World Journal of Microbiology and Biotechnology, 2007)

Operation analysis of a reservoir in GIS environment using remote sensing inputs - M. K. Goel; P. Kumar; S. K. Jain; R. S. Tiwari (International Journal of Remote Sensing, 2007)

Spatial Distribution and Seasonal Variability of Rainfall in a Mountainous Basin in the Himalayan Region - Manohar Arora; Pratap Singh; N. K. Goel; R. D. Singh (Water Resources Management, 2006)

Brackish water subirrigation for vegetables - R. M. Patel; S. O. Prasher; P. K. Goel; C. A. Madramootoo; R. S. Broughton (Irrigation and Drainage, 2003)
As freshwater resources for irrigation are being depleted rapidly, recent emphasis has been on the development of nonconventional water sources: reuse of agricultural drainage water, use of industrial or municipal wastewater, and use of brackish water for irrigation. Experiments conducted in field lysimeters over three seasons sought to investigate the feasibility of using brackish water for growing moderately sensitive crops. Brackish waters, with salinity levels of 1, 5 and 9 dS m −1 , were used. In 1993 the effects of a factorial combination of three subirrigation water salinity levels, two water table depths and four NPK fertilizer combinations on salt buildup in an initially nonsaline soil and on green pepper ( Capsicum annuum L.) performance were assessed. A gradual increase in soil solution salinity (EC sw ) from the water table to the soil surface was evident; however, throughout the growing season, the EC sw did not reach a level that could seriously damage the crop. There was no significant difference in pepper yields due to either salinity of subirrigation water or water table depth. In 1994, two potato ( Solanum tuberosum L.) cultivars were grown in the soil, which was salinized with 3.5 dS m −1 water before planting tubers. The salt buildup pattern was similar to that observed in 1993; however, the EC sw levels were higher in 1994 due to the higher initial soil salinity. Moreover, a decrease in EC sw was observed near the water table in lysimeters subirrigated with 1 dS m −1 water. For both cultivars, no significant difference in tuber yield was observed due to either water table depth or subirrigation water salinity. In 1995, three potato cultivars were grown in a nonsaline soil as well as a soil presalinized with 2 dS m −1 water. In the topsoil layer, higher rate of increase in EC sw was observed in the saline soil compared to the nonsaline soil. No significant difference in total tuber yield was observed due to either the initial soil salinity levels or subirrigation water salinity levels. Brackish water with salinity levels of up to 9 dS m −1 , when applied through subirrigation, could be used to successfully produce green peppers and potatoes under semiarid to arid conditions. Copyright © 2002 John Wiley & Sons, Ltd.

Individual and combined effect of (±)-α-hydrastine and (±)-β-hydrastine on spore germination of some fungi - M. Goel; U. P. Singh; R. N. Jha; V. B. Pandey; M. B. Pandey (Folia Microbiologica, 2003)

Evidence for new nuclear and mitochondrial genome organizations among high-frequency somatic embryogenesis-derived plants of allotetraploid Coffea arabica L. (Rubiaceae) - V. Rani; K. P. Singh; B. Shiran; S. Nandy; S. Goel; R. M. Devarumath; H. L. Sreenath; S. N. Raina (Plant Cell Reports, 2000)

Contributory presentations/posters - N. Manoj; V. R. Srinivas; A. Surolia; M. Vijayan; K. Suguna; R. Ravishankar; K. Suguna; A. Surolia; M. Vijayan; R. Schwarzenbacher; K. Zeth; Diederichs; et al. (Journal of Biosciences, 1999)

Genotypic detection of mutations in rifampicin resistant clinical isolates ofMycobacterium tuberculosis - L. M. Srivastava; Madhu Khanna; Ashish Goel; R. C. Jain (Indian Journal of Clinical Biochemistry, 1997)

Short Communication: Photoinduced sporulation in Trichoderma harzianum–an experimental approach to primary events - R. Gupta; R.K. Saxena; S. Goel (World Journal of Microbiology and Biotechnology, 1997)

Evaluation of effectiveness of a facet wiring technique: Anin vitro biomechanical investigation - Vijay K. Goel; Charles R. Clark; Kurt G. Harris; Y. E. Kim; Kary R. Schulte (Annals of Biomedical Engineering, 1989)